H3K27 demethylase KDM6B aggravates ischemic brain injury through demethylation of IRF4 and Notch2-dependent SOX9 activation - Lisha Chang; Zhaowang An; Jiang Zhang; Fuling Zhou; Dali Wang; Jian Liu; Yunhe Zhang (Elsevier, 2021)
Lysine demethylase 6B (KDM6B) is a histone H3 lysine 27 (H3K27) demethylase that serves as a key mediator of gene transcription. Although KDM6B has been reported to modulate neuroinflammation after ischemic stroke, its role in ischemic brain injury is yet to be well elucidated. Therefore, this study aimed to thoroughly demonstrate the molecular mechanism underlying the effect of KDM6B on neurological function and astrocyte response in post-ischemic brain injury. Middle cerebral artery occlusion/reperfusion (MCAO) mouse models were constructed, while the oxygen-glucose deprivation/reperfusion (OGD/R) model was developed in astrocytes to mimic injury conditions. KDM6B was upregulated post-MCAO in mice and in astrocytes following the induction of OGD/R. Silencing of KDM6B resulted in suppressed neurological deficit, reduced cerebral infarction volume, attenuated neuronal cell apoptosis, and disrupted inflammation. Dual-luciferase reporter gene and chromatin immunoprecipitation-quantitative polymerase chain reaction assays revealed that KDM6B inhibited H3K27 trimethylation in the interferon regulatory factor 4 (IRF4) promoter region, resulting in the upregulation of IRF4 expression, which in turn bound to the Notch2 promoter region to induce its downstream factor SRY-related high-mobility group box 9 (SOX9). SOX9 knockdown reversed the effects of KDM6B overexpression on ischemia-triggered brain damage. Based on these findings, we concluded that KDM6B-mediated demethylation of IRF4 contributes to aggravation of ischemic brain injury through SOX9 activation.